Cemented or Uncemented Hemiarthroplasty for Femoral Neck Fracture? Data from the Norwegian Hip Fracture Register. Issue 1 (January 2020) - Kristensen, Torbjørn B; Dybvik, Eva; Kristoffersen, Målfrid; Dale, Håvard; Engesæter, Lars Birger; Furnes, Ove; Gjertsen, Jan-Erik
Abstract: Background: A displaced femoral neck fracture in patients older than 70 years is a serious injury that influences the patient's quality of life and can cause serious complications or death. Previous national guidelines and a Cochrane review have recommended cemented fixation for arthroplasty to treat hip fractures in older patients, but data suggest that these guidelines are inconsistently followed in many parts of the world; the effects of that must be better characterized. Questions/purposes: The purpose of this study was to evaluate a large group of patients in the Norwegian Hip Fracture Register to investigate whether the fixation method in hemiarthroplasty is associated with (1) the risk of reoperation; (2) the mortality rate; and (3) patient-reported outcome measures (PROMs). Methods: Longitudinally maintained registry data from the Norwegian Hip Fracture Register with high completeness (93%) and near 100% followup of deaths were used for this report. From 2005 to 2017, 104, 993 hip fractures were registered in the Norwegian Hip Fracture Register. Fractures other than intracapsular femoral neck fractures and operative methods other than bipolar hemiarthroplasty, such as osteosynthesis or THA, were excluded. The selection bias risk on using cemented or uncemented hemiarthroplasty is small in Norway because the decision is usually regulated by tender processes at each hospital and not by surgeon. A total of 7539 uncemented hemiarthroplasties (70% women, mean age, 84 years [SD 6] years) and 22, 639 cemented hemiarthroplasties (72% women, mean age, 84 years [SD 6] years) were eligible for analysis. Hazard risk ratio (HRR) on reoperation and mortality was calculated in a Cox regression model adjusted for age, sex, comorbidities (according to the American Society of Anesthesiologists classification), cognitive function, surgical approach, and duration of surgery. At 12 months postoperatively, 65% of patients answered questionnaires regarding pain and quality of life, the results of which were compared between the fixation groups. Results: A higher overall risk of reoperation for any reason was found after uncemented hemiarthroplasty (HRR, 1.5; 95% CI, 1.4–1.7; p < 0.001) than after cemented hemiarthroplasty. When assessing reoperations for specific causes, higher risks of reoperation because of periprosthetic fracture (HRR, 5.1; 95% CI, 3.5–7.5; p < 0.001) and infection (HRR, 1.2; 95% CI, 1.0–1.5; p = 0.037) were found for uncemented hemiarthroplasty than for cemented procedures. No differences were found in the overall mortality rate after 1 year (HRR, 1.0; 95% CI, 0.9–1.0; p = 0.12). Hemiarthroplasty fixation type was not associated with differences in patients' pain (19 versus 20 for uncemented and cemented hemiarthroplasties respectively, p = 0.052) or quality of life (EuroQol [EQ]-VAS score 64 versus 64, p = 0.43, EQ5D index score 0.64 versus 0.63, p = 0.061) 1 year after surgery. Conclusions: Our study found that the fixation method was not associated with differences in pain, quality of life, or the 1-year mortality rate after hemiarthroplasty. Uncemented hemiarthroplasties should not be used when treating elderly patients with hip fractures because there is an increased reoperation risk. Level of Evidence Level III, therapeutic study.